Study on Culture Connotations of Chinese Idiomatic Phrase - Dulyala, Janya; Sae-Ueng, Waralak; Sae-Wong, Uraiwan (Journal of Graduate MCU KhonKaen Campus, 2026)
This research aims to investigate the cultural meanings, concepts, and values reflected in Chinese idiomatic expressions (惯用语) used in daily life. The study adopts the theoretical framework of Cultural Linguistics proposed by Farzad Sharifian (2011, 2017), which explains that language serves as a repository of cultural conceptualizations. The data consist of 300 Chinese idiomatic expressions, purposively selected from 1001 Chinese Idioms, Proverbs, and Slang, and analyzed through two dimensions of Cultural Linguistics: Cultural Conceptualization and Cultural Schema.The findings reveal that Chinese idiomatic expressions reflect eight domains of cultural conceptualization: imagery, interpersonal relationships, food culture, perseverance, wisdom, fate, morality and character, and physical and emotional experience. These domains are associated with five groups of cultural schemas: the schema of relationships and imagery, the schema of prudence and life wisdom, the schema of personal traits and abilities, the schema of situations and conditions, and the schema of methods and actions. The study demonstrates that Chinese idiomatic expressions used in everyday life are not merely linguistic units but profound reflections of Chinese cognitive structures, values, and worldviews. The findings can be applied to Chinese language teaching and intercultural communication, enhancing learners’ cultural understanding and communicative competence.